Assessment of the relationship between serum uric acid levels and oxidative stress markers in patients with uncomplicated type 2 diabetes mellitus - Kaya, Esat Kıvanç; Çandar, Tuba; Ergün, İhsan (Acta Medica, 2024)
Objective: Type 2 Diabetes Mellitus is a worldwide health issue characterized by hyperglycemia due to defects in insulin secretion, insulin action, or both, and is associated with significant negative health outcomes. Oxidative stress plays a crucial role in the onset, progression, and complications of this disorder. Elevated serum uric acid level is an independent predictor of vascular complications in diabetic patients, and hyperuricemia may contribute to oxidative stress. The objective of this study is to examine the correlation between increased serum uric acid levels and the markers of oxidative stress, including ischemia-modified albumin (IMA), total oxidant status (TOC), and total antioxidant capacity (TAC), in type 2 diabetic patients who don’t have vascular complications. Materials and Methods: A total of 73 individuals were enrolled in the study including 20 type 2 diabetic patients with high serum uric acid levels (> 6.5 mg/dl), 21 type 2 diabetic patients with normal serum uric acid levels (< 6.5 mg/dl), and 32 healthy individuals. Ischemia-modified albumin, total oxidant status, and total antioxidant status levels were compared between patient groups and the control group Results: As a result of this study, there was no significant association between serum uric acid levels and ischemia-modified albumin, total oxidant status, and total antioxidant status levels in type 2 diabetic patients. Conclusions: This study concluded that high serum uric acid levels do not directly affect oxidative stress in type 2 diabetic patients without vascular complications.